3, 4‐Bis(hydroxymethyl)hexane‐1, 6‐diol‐based Maltosides (HDMs) for Membrane‐Protein Study: Importance of Detergent Rigidity–Flexibility Balance in Protein Stability. Issue 24 (8th November 2022) - Lee, Hyun Sung; Das, Manabendra; Mahler, Florian; Ahmed, Waqar; Wang, Haoqing; Mortensen, Jonas S.; Hariharan, Parameswaran; Ghani, Lubna; Byrne, Bernadette; Guan, Lan; Loland, Claus J.; Keller, Sandro; et al.
Abstract: Detergents have been major contributors to membrane‐protein structural study for decades. However, membrane proteins solubilized in conventional detergents tend to aggregate or denature over time. Stability of large eukaryotic membrane proteins with complex structures tends to be particularly poor, necessitating development of novel detergents with improved properties. Here, we prepared a novel class of detergents, designated 3, 4‐bis(hydroxymethyl)hexane‐1, 6‐diol‐based maltosides (HDMs). When tested on three membrane proteins, including two G‐protein‐coupled receptors (GPCRs), the new detergents displayed significantly better behaviors compared with DDM. Moreover, the HDMs were superior or comparable to LMNG, an amphiphile widely used for GPCR structural study. An optimal balance of detergent rigidity vs. flexibility of the HDMs is likely responsible for their favorable behaviors toward membrane‐protein stability. Thus, the current study not only introduces the HDMs, with significant potential for membrane‐protein structural study, but also suggests a useful guideline for designing novel detergents for membrane‐protein research. Abstract : The current study introduces newly designed detergents (HDMs) that conferred enhanced stability to a few membrane proteins compared to DDM and LMNG, and illustrates the importance of detergent rigidity‐flexibility balance for membrane‐protein stability.